2010
DOI: 10.1007/s00784-010-0471-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and antibacterial effect of an anti-inflammatory toothpaste formulation with Scutellaria baicalensis extract on experimental gingivitis

Abstract: It was the aim of the study to evaluate the clinical and antibacterial effect of a dentifrice containing an anti-inflammatory plant extract (SB) versus a placebo (PLA) using an experimental gingivitis model. Forty subjects (20 per group) discontinued all oral hygiene measures for four teeth for a period of 21 days using a shield (to generate a possible gingivitis) while they could brush the other teeth normally. After brushing, the shield was removed and teeth were treated with the randomly assigned toothpaste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…The PubMed-MEDLINE, Cochrane CENTRAL, IndMed, and other sources identified 1378 unique records which were screened by title and abstract [ Figure 2 ]. After full-text reading, 10 records[ 15 16 17 27 28 29 30 31 32 33 ] were excluded. This exclusion resulted in 19 full-text articles plus 3 unpublished records.…”
Section: Resultsmentioning
confidence: 99%
“…The PubMed-MEDLINE, Cochrane CENTRAL, IndMed, and other sources identified 1378 unique records which were screened by title and abstract [ Figure 2 ]. After full-text reading, 10 records[ 15 16 17 27 28 29 30 31 32 33 ] were excluded. This exclusion resulted in 19 full-text articles plus 3 unpublished records.…”
Section: Resultsmentioning
confidence: 99%
“…Wogonoside is a main constituent of the herb [2,3,6] . In this study, using a panel of human cancer cell lines selected from three of the most common human cancers, including colorectal cancer (SW-480, HCT-116 and HT-29), non-small cell lung cancer (NSCLC), and breast cancer (MCF-7 and MDA-MB-231), we observed that wogonoside did not show obvious antiproliferative effects.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic approaches aimed at modulating the host response, did involve polyphenols from Cranberries (Vaccinium macrocarpon) extracts, and led to beneficial effects slowing the periodontal disease progression [162]. In this field, polyphenols have also been considered for applications [163] in helping to control the oral hygiene, through the use of toothpastes enriched with 0.1% extracts containing naringenin and quercetin [164] and 0.5% extracts containing baicalein, baicalin, and wogonin [165] and through the use of polyphenol-containing gels [166].…”
Section: Development Of Ti Surfaces Functionalized With Polyphenolsmentioning
confidence: 99%